A wolf called Wander - Parry, Rosanne (Greenwillow Books, an imprint of HarperCollins Publishers, 2019)
I have a brother. Sharp. Bigger than me, and all growl. I have sisters. Pounce, who loves to wrestle, and Wag, who talks with her tail. And best of all, my brother Warm, who likes to curl up under my chin, the only pup smaller than me. Swift, a wild wolf cub, lives with his pack in the mountains. When a rival pack attacks, Swift and his family scatter, and Swift sets out on an incredible journey through dense forests, into barren wilderness, and across flowing water. The trip is dangerous and full of peril, and Swift encounters fire, hunger, hunters, and highways as he wanders. Will Swift find the courage to survive? Will he ever find a place to call home? A Wolf called Wander is based on the extraordinary true story of a wolf named OR-7 (and often called Journey) - a wild wolf who traveled a remarkable 1,000 miles across the Pacific Northwest. --